LOCALIZATION OF HYALURONIC ACID IN SYNOVIAL CELLS BY RADIOAUTOGRAPHY - Barland, Peter (The Rockefeller University Press, 1968)
Cultured human synovial cells secrete hyaluronic acid (HA) into the culture medium. Glucosamine-6-(3)H was shown to be a direct and relatively specific precursor of HA-(3)H by the following observations: the susceptibility of nondialyzable radioactivity in the medium to hyaluronidase, its migration with hexuronic acid on zone electrophoresis in polyvinyl chloride, its exclusion from Sephadex G-200, and the localization of radioactivity to glucosamine after hydrolysis of the labeled polysaccharide. The presence of intracellular HA-(3)H was established by sequential extraction of labeled cells and by radioautography of synovial cell cultures digested with hyaluronidase in situ. When cells were exposed to medium lacking glucose, glucosamine-(3)H-uptake was enhanced; and this made possible electron microscopic radioautographic studies. These studies demonstrate the early and continued presence of HA-(3)H within the Golgi apparatus.